Trajectories of Physical Activity Predict the Onset of Depressive Symptoms but Not Their Progression: A Prospective Cohort Study - Kaseva K; Rosenström T; Hintsa T; Pulkki-Råback L; Tammelin T; Lipsanen J; Yang X; Hintsanen M; Hakulinen C; Pahkala K; Hirvensalo M; Hutri-Kähönen N; et al. (My University, 2022)
This prospective, community-based study examined trajectories of physical activity from childhood to adulthood and whether these trajectories contributed to depressive symptoms in adulthood to a greater degree than adulthood physical activity. Participants () were from the ongoing Cardiovascular Risk in Young Finns Study which started in 1980. Depressive symptoms were measured with Beck Depression Inventory (BDI-II) in 2012, and physical activity was assessed from 1980 to 2011 with self-reports. Analyses were adjusted for age, sex, childhood negative emotionality, socioeconomic factors, previous depressive symptoms, social support, body mass index, and smoking status (1980–2007). Highly, moderately, and lightly physically active trajectory groups were identified. Highly active participants reported lower levels of depressive symptoms compared to lightly active ones () and compared to moderately active ones (). Moderately active participants had less symptoms than lightly active ones (). High levels of adulthood physical activity associated with lower levels of depressive symptoms (). The findings did not withstand adjustment for previous depressive symptoms (). Lifelong physical activity trajectories or adulthood physical activity was not associated with the progression of depressive symptoms in adulthood. Thus, physical activity history does not contribute to the progression of the depressive symptoms to a greater degree than adulthood physical activity.